2012
DOI: 10.1108/13555851211192678
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effect of country‐of‐origin, brand equity and purchase involvement on consumer purchase intentions of clothing labels

Abstract: PurposeThis study, conducted in Thailand, aims to examine the effect of interaction of country‐of‐origin (COO), brand equity and product purchase involvement on consumers' evaluation and purchase preference of Thai brands of fashion apparel made in three nominated Asian countries of varying levels of manufacturing competence.Design/methodology/approachData from a field survey were analyzed through a 2×2×3 factorial design and the influence of a particular factor over the others in specific scenarios was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 28 publications
1
56
0
1
Order By: Relevance
“…Many researchers report that, consumers prefer products made by developed countries over those from less developed countries (Lee & Lee, 2011;Lee et al, 2013;Ha-Brookshire & Yoon, 2012). The Global Competitive Index GCI shows the ranks of each country among the world countries (Parkvithee & Miranda, 2012). The literature of Moradi & Zarei, (2012), has also shown that consumer brand image changes as the brands are made in different countries.…”
Section: Country-of-origin Coomentioning
confidence: 99%
“…Many researchers report that, consumers prefer products made by developed countries over those from less developed countries (Lee & Lee, 2011;Lee et al, 2013;Ha-Brookshire & Yoon, 2012). The Global Competitive Index GCI shows the ranks of each country among the world countries (Parkvithee & Miranda, 2012). The literature of Moradi & Zarei, (2012), has also shown that consumer brand image changes as the brands are made in different countries.…”
Section: Country-of-origin Coomentioning
confidence: 99%
“…The other point that studies demonstrate is that people care about which country products come from and where they are made and consider these factors when evaluating the quality of products, (Parkvithee & Miranda, 2012).…”
Section: Background Of Country Of Originmentioning
confidence: 99%
“…The empirical findings indicate that the factors such as attitudes and brand loyalty have effective role in creating involvement in product choice (Foxall, Goldsmith, & Brown, 1998). A brand value and involvement in the product purchase is effective in the product evaluation by consumer (Parkvithee & Miranda, 2012). The involvement level can be related to the media type and the consumer's behaviors in the purchase decision (Josiam, Kinley, & Kim, 2005;Huang, Chou, & Lin, 2010).…”
Section: H1-1: the Personal Factors Influence The Consumer Purchase Dmentioning
confidence: 95%